Analisis Pendapatan Usahatani Pepaya (Studi Kasus Di Desa Lembean Kecamatan Kauditan Kabupaten Minahasa Utara) - Soba, Esterlita; Rori, Yolanda Pinky Ivanna; Pangemanan, Paulus Adrian (AGRI-SOSIOEKONOMI, 2023)
This research aims to analyze papaya farming income in Lembean Village, Kauditan District, North Minahasa Regency. This research was conducted from April 2022 to June 2022. The data used in this research is primary data obtained through direct interviews with 3 respondents using a list of questions/interviews. Secondary data was obtained through books, journals and literature related to this research topic. The results of this research show that the average income from papaya farming is IDR 28,364,528 from Bangkok papaya revenues of IDR 50,160,000 per harvest. With an average total cost of IDR 10,871,824 for a total. The R/C ratio is more than one with a value of 3.2, which means that every rupiah spent in farming will receive income of IDR 3.2.